Optimizing Virtual Machine Placement Using Intelligent Water Drop and Simulating Algorithm - Ramakant, VO; Victor, A (International Journal of Computer Sciences and Engineering, 2025)
Developing approaches intended to produce top notch answers for tackle troublesome computational enhancement issues by playing out a pursuit over the space of heuristics as opposed to looking the arrangement space specifically. Significant progress in developing search methodologies for a huge variety of application areas still require specialists to integrate their expertise in every problem domain. Researchers have need for developing automated systems to replace the role of a human expert. A hyper-heuristic for the most part goes for diminishing the measure of area information in the inquiry system. Coming about approach ought to be shabby and quick to execute, requiring less mastery in either the issue area or heuristic techniques and it would be vigorous. Resulting approach is cheap and fast to implement, requiring less expertise in either the problem domain as well as hyper heuristic methods and it would be robust.